1983
DOI: 10.1128/jcm.17.2.202-217.1983
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a computer-assisted, kinetics-based enzyme-linked immunosorbent assay for detection of coronavirus antibodies in cats

Abstract: A computer-assisted, kinetics-based enzyme-linked immunosorbent assay was adapted for the detection of coronavirus antibodies in feline serum. An alkaline antigen diluent (carbonate-bicarbonate buffer, pH 9.6) used in initial experiments produced diffuse, nonspecific color reactions in both viral and control antigen cuvettes which were correlated, paradoxically, with coronavirus antibody levels in test sera. These interfering reactions were minimized by use of lower-pH antigen diluents such as water and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…FCoV is distributed worldwide in household and wild cats [27,28]. The virus is endemic especially in environments in which many cats are kept together in a small space (eg, catteries, shelters, pet stores).…”
Section: Prevalencementioning
confidence: 99%
“…FCoV is distributed worldwide in household and wild cats [27,28]. The virus is endemic especially in environments in which many cats are kept together in a small space (eg, catteries, shelters, pet stores).…”
Section: Prevalencementioning
confidence: 99%
“…Sahu et al [29] found the ELISA markedly superior to the complement-fixation and certain other serological tests for the detection of CEM-infected mares. However, even using the kinetics-based ELISA or KELA system, which is a highly sensitive technique for quantitation of serum antibody levels [17], very little evidence was found to indicate that the cats in this study, even those that became infected, responded serologically on single or repeated exposure to CEMO.…”
Section: Discussionmentioning
confidence: 70%
“…The KELA procedure was essentially similar to that described by Jacobson et al [16] and Barlough et al [17]. Assays were conducted on Gilford EIA-PR50's (Gilford Instruments, Inc., Oberlin, OH) interfaced with a PDP11/34A computer (Digital Instru-ment Corp, Maynard, MA).…”
Section: Rechallenge Experimentsmentioning
confidence: 99%
“…globulin associated) of serum samples to the antigen preparations is often an additional problem. It has been described that most but not all of false-positive reactions are attributable to recent vaccination [17,27,30,31]. Some kinds of cell culture vaccines prepared for use in cats have been commonly utilized in Japan as well.…”
Section: Discussionmentioning
confidence: 99%